Myxomycetes in the virgin beech and old-aged spruce forests of National Nature Park “Bewitched Land” (Ukrainian Carpathians) - Dudka, I.O.; Kryvomaz, T.I. (My University, 2013)
Mycological observations in virgin beech and old-aged spruce forests of National Nature Park (NNP) “Bewitched Land” carried out in July 2011 allowed to reveal 20 myxomycete species. Ceratiomyxa fruticulosa belongs to subclass Ceratiomyxomycetidae, other 19 species are representatives of subclass Myxogastromycetidae, assigned to four orders: Trichiales (8 species), Physarales (5), Liceales and Stemonitales (on 3 species each). The highest frequency of occurrence was noted for Ceratiomyxa fruticulosa, Arcyria cinerea and Lycogala epidendrum. Dictydiaethalium plumbeum was determined as the species with rather limited distribution in Ukraine and the Ukrainian Carpathians, especially. Investigation of myxomycete substrate preferences showed that the most important woody species that supported development of the majority of slime molds in NNP “Bewitched Land” were spruce (Picea abies) and beech (Fagus sylvatica). Unlike the Carpathian biosphere reserve and NNP “Skolivski Beskydy” where myxomycetes predominantly used beech wood as a substrate myxomycete biota of “Bewitched Land” showed reverse type of substrate association preferring the wood of coniferous tree – spruce.
Keywords: myxomycetes; slime molds; virgin forests; old-aged forests; taxonomic diversity; substrate preferences; 582.241: 581.526.42 (234.372.3)